Water Management and Monitoring Practices in Hospitals—United States, 2018. (October 2020) - Stuckey, Matthew J.; Arduino, Matthew; Edens, Chris; Dudeck, Margaret; Pollock, Daniel; Fagan, Ryan
Abstract : Background: Water management programs (WMPs) are needed to minimize the growth and transmission of opportunistic pathogens in healthcare facility water systems. In 2017, the Centers for Medicare & Medicaid Service (CMS) began requiring that certified hospitals in the United States have water management policies and procedures; in response, the National Healthcare Safety Network (NHSN) Annual Hospital Survey included new, voluntary questions on practices regarding water management and monitoring. Of 4, 929 hospitals surveyed in 2017, 3, 821 (77.5%) reported having a WMP. Of these 3, 821 facilities, 86.9% reported regular monitoring of water temperature; 66.2% monitored disinfectant (eg, residual chlorine); 63.1% used specific tests for Legionella ; and 35.6% performed heterotrophic plate counts (HPCs). We analyzed new, 2018 hospital survey data to assess further progress toward meeting CMS requirements for WMPs. Methods: We analyzed 2018 NHSN Annual Hospital Survey responses for facilities that reported on WMPs in 2017. Responses included information regarding risk assessments for Legionella and other waterborne pathogens as well as details regarding WMP teams and water-monitoring practices. WMP team members were categorized as administrative (hospital administrator, compliance officer, risk or quality management), epidemiology or infection control (epidemiologist or infection preventionist, other clinical), or environmental or facilities (consultant, facility manager or engineer, equipment or chemical supplier, maintenance). Statistical significance was assessed using the McNemar test, where appropriate. Results: Of hospitals reporting on WMPs in 2017, 4, 087 of 4, 929 (83%) responded again in 2018. The proportion of facilities that reported having a WMP increased from 3, 258 of 4, 087 (79.7%) in 2017 to 3, 647 of 4, 087 (89.2%) in 2018 ( P < .0001). Of the 3, 647 hospitals that reported having a WMP in 2018, 95.9% had conducted a risk assessment for waterborne pathogens; 67.3% of these facilities had most recently done so within 1 year of the survey. WMP teams had representation from environmental or facilities staff at 98.8% of hospitals, epidemiology or infection control staff at 89.8% of hospitals, and administrative staff at 71.7% of hospitals. Of facilities with WMPs in 2018, 90.5% reported regular monitoring of water temperature, 72.2% disinfectant, 67.4% tests for Legionella, and 48.8% HPCs. Conclusions: More hospitals reported having a WMP in 2018 than 2017. However, ~1 in 10 respondents lacked a WMP. Differences in water monitoring practices across facilities potentially reflect a lack of standardization in how WMPs are implemented. Some hospital WMPs do not incorporate routine monitoring of water temperature and disinfectant, which is a basic practice. CDC continues to develop tools, resources, and training to support facility WMP teams in meeting CMS requirements and protecting patients from water-associated pathogens. Funding: None Disclosures: None